Virtual reality-induced dopamine reward hypothesis for opioid addiction - Sarah Katz (Advancements in Health Research, 2026)
While the opioid epidemic continues to plague the globe, scant research exists into the opportunities of virtual reality (VR) therapy for opioid addiction treatment. Furthermore, few to no studies have explored the potential of VR as a dopamine replacement solution for the dopamine deficiency caused by opioid withdrawal. Therefore, this theoretical research article sought to address this research gap by proposing a hypothesis framework involving VR exposure immediately following administration of the tapered opioid medication to help the patient associate the opioid-induced reward experience with the simulation. This method would then compare dopamine levels during VR exposure to corresponding levels 20 minutes following administration of the medication to assess whether the reward memory from the VR experience has the capacity to essentially compensate for dopamine deficiency during opioid withdrawal.